Pengaruh Model Pembelajaran Kooperatif Tipe STAD (Student Team Achievement Divisions) terhadap Hasil Belajar Siswa Kelas VIII MTs Islam Babussalam pada Materi Persamaan Linear Dua Variabel - Sabrun, Sabrun (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
This research aims to determine the effect of the Student Team Achievement Divisions (STAD) type cooperative learning model on MTs student learning outcomes. Islam Babussalam on two-variable linear equations for the 2022/2023 academic year. This research is a experimental research. The experimental design used was one group pre test post test. The subjects of this research were 20 students of MTs Islam Babussalam class VIII. This research used one class that was treated with the STAD model. The analysis technique uses the t test. Based on the research results, it shows that the pre test results are 8.08 and the post test results are 15.18. So we get t_count=9.087 and t_(table )=1.685, we get t_count≥ t_(table ). Thus, it is concluded that there is an influence of the STAD type cooperative model on the learning outcomes of MTs Islam Babussalam students in the two-variable linear equation material for the 2022/2023 academic year.